ASEAN Cooperation in Creating Sustainable Development in the Food Sector: Opportunities and Challenges - Dini Putri Saraswati; Shanti Darmastuti; Jati Satrio (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
This study aims to analyze the opportunities and challenges faced by ASEAN cooperation in creating sustainable development in the food sector. The method used in this study is a qualitative descriptive analysis which involves searching the literature from sources that are relevant to the research topic. ASEAN already has various cooperation mechanisms in the food sector. In addition, the trend also shows an increase in food trade in the ASEAN region. ASEAN as a region has a huge opportunity to increase cooperation in the food sector, considering there are still large opportunities to add value to products. ASEAN is a region that produces various food commodities and also has various research and development centres for agricultural commodities. However, even though it has great opportunities, there are several challenges in realizing this dream, including infrastructure challenges and pandemic challenges.